(3dhGeY GdCSQGQ TQM eWGdY GdCfhGQs - (3bWH GdOjf eMeO Hf eMeO GdQGRis; (3SQGL GdOjf eMehO Hf CHj HcQ GdGQehj,J (B682 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg ajGV PhGQa GdYhGQa hHYO aEf GdYdhe Ydi JTYH afhfgG hSejJgG dhGeY GdCSQGQ ai TQM eWGdY GdCfhGQ s
(3BNQgG (B:s
(3hCeG GdQSe GdJGe hGdfGbU adLhGR Cf jPcQ ajgeG NhGU eJYOOI hajg eG YQaJ hdfbJUQ Ydi gPG GdbOQ ef GdcdGe ai bSe GdJUhQGJ hGddg CYde HGdUhGH hEdjg eQLY GdeBH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1715s
Keywords: (3GdadSaI hGdefWbs